Bridging the Methodological Gap: Emic and Etic Paradigms in Evolving the Living Hadith Studies: Menjembatani Kesenjangan Metodologis: Paradigma Emik dan Etik dalam Perkembanganan Studi Living Hadis - Rizkiy, M. Inul (Jurnal Living Hadis, 2025)
The study of living hadith, while demonstrating the advancement of hadith scholarship, nonetheless leaves considerable room for further development. Moreover, researchers' awareness of the reality of hadith as a foundation for rituals still requires methodological strengthening, particularly concerning whether interpretations arise from the reception of practitioners within the tradition (emic) or from the researcher's own analysis (etic). This article aims to explore more deeply the concepts of emic and etic in living hadith studies, as well as their application in this field of research. Concretely, two fundamental questions form the basis of this study: First, how are emic and etic constructed in living hadith research? Second, what are the patterns of distribution of emic and etic within the dynamics of living hadith studies? These questions are examined using a systematic literature review approach, with data sourced from Google Scholar using the keywords "living hadis," "living sunnah," and "living hadith." The study data were limited to journals accredited by Sinta or Scopus and published between 2021 and 2025. Through data exclusion, 37 relevant articles were identified. The findings reveal four patterns of engaging with hadith: emic (16 articles), etic (16 articles), emic-etic (4 articles), and traditions not based on hadith (one article). Furthermore, within the five-stage research framework proposed by Saifuddin Zuhri, an etic approach is applied in the analysis of practice, an emic approach in the examination of reception and text, and an etic approach in the study of transmission and transformation.